Nonlinear pricing - Armstrong, C (Annual Reviews, 2016)
I examine the use of nonlinear pricing as a method of price discrimination, both with monopoly and oligopoly supply. Topics covered include an analysis of when it is profitable to offer quantity discounts and bundle discounts, connections between second- and third-degree price discrimination, the use of market demand functions to calculate nonlinear tariffs, the impact of consumers with bounded rationality, bundling arrangements between separate sellers, and the choice of prices for quality upgrades and add-on products.